Analysis of the Quality Clean Water Sources through Geographic Information System Mapping and Geoelectric Methods in Flood-Prone Areas - Lenie Marlinae; Danang Biyatmoko; Husaini; Chairul Irawan; Syamsul Arifin; Akhmad R Saidi; Abdi Fithria; Bibin Bintang Andriana; Tien Zubaidah; M. Ratodi; Ammara Ulfa Azizah (Universitas Airlangga, 2025)
Introduction: Astambul Subdistrict in Banjar Regency is classified as a flood-prone area. Such regions tend to experience a decline in clean water quality. In Astambul, no mapping has been conducted regarding clean water quality based on water management and land conditions to improve clean water quality in flood-prone areas. This study aims to analyze the availability of clean water sources in flood-prone areas using geoelectrical methods and Geographic Information Systems (GIS). Methods: This study used a quantitative research design with a cross-sectional method to analyze clean water sources using geoelectric and Geographic Information System (GIS) methods. This study was conducted in five villages in Banjar Regency, South Kalimantan Province. Testing using the geoelectrical method was conducted at five locations in five villages, while the GIS method was used at 30 locations across the five villages. Results and Discussion: The geoelectric method showed that 4 villages had turbid water quality, and 1 village had very turbid water. The GIS (Geographic Information System) method indicated that the parameters for turbidity, iron (Fe), manganese (Mn), and coliforms did not meet the standards. The average values of Dissolved Oxygen (DO), Total Dissolved Solids (TDS), Total Suspended Solids (TSS), and turbidity are 8.03 mg/L, 179.27 mg/L, 0.22 mg/L, and 17.23 NTU, respectively. The average values for pH, iron (Fe), and manganese (Mn) are 6.44, 0.68 mg/L, and 21.02 mg/L, respectively. Conclusion: Based on Geoelectric and Geographic Information System analysis, the Astambul District area has clean water sources that are still below quality standards.